Desarrollo del manual de consulta para el área de desarrollo humano de una empresa de retail-financiero - García Garaicoa, Francisco Xavier (2010)
This professional work, was made in one of the biggest Corporative Enterprises in the nation, integrated by companies filled with tradition: A financial institution, dedicated to massive financial which name is a symbol of tradition in our country; an Insurance company, a Travel Agency, and a Textile company, dedicated to the elaboration of garments. This companies together, created synergy to develop a business model of Financial Retailing, which they currently manage. This Group, has the compromise to achieve every goal they have proposed, and a vision of acquiring excellence in client service in each and every single one of the companies it runs. It went through a program during 2007, along with Managers, Supervisors, and the rest of the personnel. This Group, initiated the challenge of seeking continuous improvement and process reengineering focused on 6 specific areas, one of which was the area of Human Development. Human Development area was created in 2005, after realizing that the companies needed to develop the human beings working for them, in a complete way. Basically the area is divided into two branches: Personnel Management, which includes payroll payments, contracts, promotions, salary raises, etc… And the Recruiting branch, which includes Hiring, , Training and Development, which groups development activities for collaborators since their hiring, professional development, growth th As a product of the improvement project that took place through the entire organization, in 2007 the Human Development area took a further boost by adopting new concepts of management indicators, feedback meetings, created Committees in order to monitor the Organization and the development of other projects in the area. By handling the area in this way, the personell had develop a long term vision, making the Group one of the “Great Place to Work”, recognized in the country. To maintain and promote this initiatives, a Reference Manual has been developed, so current collaborators in the area, manages in a regulated basis, processes and subsystems, and it works as well for managers and employees of various departments, for recruitment, compensation, staff development and untying.